Among the wicked [compact disc, unabridged] : a Kate Burkholder novel - Castillo, Linda (Castillo, Linda. Kate Burkholder novel., 2016)
Chief of Police Kate Burkholder is called upon by the sheriff's department in rural, upstate New York to assist on a developing situation that involves a reclusive Amish settlement and the death of a young girl. Unable to penetrate the wall of silence between the Amish and English communities, the sheriff asks Kate to travel to New York, pose as an Amish woman, and infiltrate the community. Kate goes deep under cover. In the coming days, she unearths a world built on secrets, a series of shocking crimes, and herself, alone, trapped in a fight for her life.